Fuzzy Graph Theory with Applications to Human Trafficking - Mordeson, John N.; Mathew, Sunil; Malik, Davender S.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book reports on advanced concepts in fuzzy graph theory, showing a set of tools that can be successfully applied to understanding and modeling illegal human trafficking. Building on the previous book on fuzzy graph by the same authors, which set the fundamentals for readers to understand this developing field of research, this second book gives a special emphasis to applications of the theory. For this, authors introduce new concepts, such as intuitionistic fuzzy graphs, the concept of independence and domination in fuzzy graphs, as well as directed fuzzy networks, incidence graphs and many more. .
Strengthening and Weakening Members of a Network -- Domination in Fuzzy Graphs -- Fuzzy Incidence Graphs -- Networks -- Complementary Fuzzy Incidence Graphs -- Human Traﬃcking: Source, Transit, Destination Designations -- Human Traﬃcking: Policy Intervention.
Keywords: Computational intelligence; Graph theory; Computer simulation; International criminal law; Game theory; Computational Intelligence; Graph Theory; Computer Modelling; International Criminal Law; Game Theory